PENERAPAN MODEL SOMATIC, AUDITORY, VISUAL, INTELEKTUAL (SAVI) UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 47 SURAKAN - Kasmawati; Ilham Assidiq; Nadar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low activeness and learning outcomes of students in the Mathematics subject of Grade IV at SD Negeri 47 Surakan. The purpose of this study is to improve students' activeness and mathematics learning outcomes through the application of the Somatic, Auditory, Visual, Intellectual (SAVI) learning model. This type of research is Classroom Action Research (CAR) conducted in two cycles. This study uses the Kammis and McTaggart model which consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were 13 Grade IV students of SD Negeri 47 Surakan. Data collection techniques were carried out through observation, tests, and documentation. The research results show that the implementation of the SAVI learning model can increase student activeness and learning outcomes. Student activeness increased from 41% in the pre-action phase to 62% in cycle I, and increased to 87% in cycle II. In addition, student learning outcomes also increased, from 31% in the pre-action phase to 62% in cycle I, and increased to 85% in cycle II. Thus, it can be concluded that the implementation of the Somatic, Auditory, Visual, Intellectual (SAVI) learning model can improve the activeness and mathematics learning outcomes of fourth-grade students at SD Negeri 47 Surakan.